Data For "The Extremely Active 2017 North Atlantic Hurricane Season" - Klotzbach, Philip; Schreck III, Carl; Collins, Jennifer; Bell, Michael; Blake, Eric; Roache, David (Zenodo, 2018)
This repository includes the Atlantic hurricane data, climate indices and scripts used to generate the tables and figures in the paper entitled: "The Extremely Active 2017 North Atlantic Hurricane Season".